Creation lake ebook A novel. - Kushner, Rachel (2024)
*SHORTLISTED FOR THE 2024 BOOKER PRIZE* *LONGLISTED FOR THE 2024 NATIONAL BOOK AWARD* *LONGLISTED FOR THE 2025 PEN FAULKNER AWARD FOR FICTION* *AN INSTANT NEW YORK TIMES BESTSELLER* *NAMED A BEST BOOK OF 2024 BY THE NEW YORK TIMES, THE ATLANTIC, VULTURE, VOGUE, THE WASHINGTON POST, KIRKUS REVIEWS, NPR, THE ECONOMIST, THE CHICAGO PUBLIC LIBRARY, VOX, and more* From Rachel Kushner, two-time finalist for both the Booker Prize and National Book Award, a "vital" ( The Washington Post ) and "wickedly entertaining" ( The Guardian ) novel about a seductive and cunning American woman who infiltrates an anarchist collective in France—a propulsive page-turner filled with dark humor. Creation Lake is a novel about a secret agent, a thirty-four-year-old American woman of ruthless tactics and clean beauty who is sent to do dirty work in France. "Sadie Smith" is how the narrator introduces herself to the rural commune of French subversives on whom she is keeping tabs, and to her lover, Lucien, a young and well-born Parisian she has met by "cold bump"—making him believe the encounter was accidental. Like everyone she targets, Lucien is useful to her and used by her. Sadie operates by strategy and dissimulation, based on what her "contacts"—shadowy figures in business and government—instruct. First, these contacts want her to incite provocation. Then they want more. In this region of old farms and prehistoric caves, Sadie becomes entranced by a mysterious figure named Bruno Lacombe, a mentor to the young activists who believes that the path to emancipation is not revolt but a return to the ancient past. Just as Sadie is certain she's the seductress and puppet master of those she surveils, Bruno is seducing her with his ingenious counter-histories, his artful laments, his own tragic story. Written in short, vaulting sections, Rachel Kushner's rendition of "noir" is taut and dazzling. Creation Lake is Kushner's finest achievement yet—a work of high art, high comedy, and unforgettable pleasure.